2020
DOI: 10.1088/1742-6596/1492/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol)-based thin films for optical humidity sensing

Abstract: The optical and humidity-sensing properties are studied of hydrophobically modified PVA, namely poly(vinyl alcohol-co-vinyl acetal)s of varied copolymer composition. Copolymers are synthesized by reacting PVA with acetaldehyde in aqueous solution, thus introducing cyclic acetal functionalities in the polymer chain. Thin polymer films are deposited by spin-coating and their optical properties are studied as a function of the copolymer composition, i.e., degree of acetalization. Reflectance measurements at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…So, in this case, the highest n is observed for the copolymer of intermediate modification degree, unlike samples annealed at 60 °C, in which case the refractive index was found to decrease gradually with increasing acetal content [13]. Figure 1b shows the percentage decrease in thickness of films annealed at 180 °C compared to films annealed at 60 °C [13]. From the calculated values, it can be seen that the thicknesses of all films decreased when they were annealed at 180 °C.…”
Section: Methodsmentioning
confidence: 69%
See 4 more Smart Citations
“…So, in this case, the highest n is observed for the copolymer of intermediate modification degree, unlike samples annealed at 60 °C, in which case the refractive index was found to decrease gradually with increasing acetal content [13]. Figure 1b shows the percentage decrease in thickness of films annealed at 180 °C compared to films annealed at 60 °C [13]. From the calculated values, it can be seen that the thicknesses of all films decreased when they were annealed at 180 °C.…”
Section: Methodsmentioning
confidence: 69%
“…In the literature, a number of papers report on the application of PVA-based composite films as active media for humidity sensing [9][10][11][12], but to the best of our knowledge PVA copolymers were not tested in optical sensors. We have already shown that films of poly(vinyl alcohol-co-vinyl acetal)s of varied copolymer compositions annealed at 60 °C can be used as active media for optical sensing of humidity [13]. The comparison with pure PVA thin films confirms the positive influence of acetal fraction in the copolymer on sensing properties.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations